Eugenol nanoemulsion inactivates Listeria monocytogenes, Salmonella Enteritidis, and Escherichia coli O157:H7 on cantaloupes without affecting rind color - Balasubramanian, Brindhalakshmi; Shah, Trushenkumar; Allen, Jodie; Rankin, Kimberly; Xue, Jingyi; Luo, Yangchao; Mancini, Richard; Upadhyay, Abhinav (Frontiers in Sustainable Food Systems, 2022)
Listeria monocytogenes, Salmonella Enteritidis, and Escherichia coli O157:H7 are the major foodborne pathogens that have been implicated in outbreaks related to consumption of contaminated cantaloupes. Current chlorine-based decontamination strategies are not completely effective for inactivating the aforementioned pathogens on cantaloupes, especially in the presence of organic matter. This study investigated the efficacy of eugenol nanoemulsion (EGNE) wash treatments in inactivating L. monocytogenes, Salmonella spp., and E. coli O157:H7 on the surface of cantaloupes. In addition, the efficacy of EGNE in inhibiting the growth of the three pathogens on cantaloupes during refrigerated and room temperature storage of 5 days was investigated. Moreover, the effect of EGNE wash treatment on cantaloupe color was assessed using a Miniscan® XE Plus. The EGNE was prepared with either Tween 80 (TW) or a combination of Gum arabic and Lecithin (GA) as emulsifiers. The cantaloupe rind was washed with EGNE (0.3, 0.6 & 1.25%), in presence or absence of 5% organic load, for 1, 5, or 10 min at 25℃. Enumeration of surviving pathogens on cantaloupe was performed by serial dilution and plating on Oxford, XLD or SMA agar followed by incubation at 37℃ for 24-48 h. EGNE-GA and EGNE-TW wash significantly reduced all three pathogens by at least 3.5 log CFU/cm2 as early as 5 minutes after treatment. EGNE-GA at 1.25% inactivated L. monocytogenes, E. coli O157:H7 and S. Enteritidis on cantaloupes to below the detectable limit within 5 and 10 minutes of treatment, respectively ( 4 log CFU/cm2, P<0.05). EGNE treatments significantly reduced the survival of L. monocytogenes, S. Enteritidis, and E. coli O157:H7 on cantaloupe by at least 6 log CFU/cm2 at day 5 of storage at 25 and 4℃ (P<0.05). Presence of organic matter did not modulate the antimicrobial efficacy of nanoemulsion treatments (P>0.05). EGNE treatments did not affect the rind color of cantaloupes (P>0.05). In conclusion, eugenol nanoemulsions could potentially be used as a natural sanitizer to inactivate foodborne pathogens on cantaloupes. Further investigations in an industry setting are warranted.